PROBLEMS AND SOLUTIONS OF PROTECTING MOTHERHOOD AND CHILDHOOD IN UZBEKISTAN IN THE 1920S-1960S (In the Case of the Southern Regions) - N. D. Toshtemirova (Modern American Journals, 2025)
Research on the protection of motherhood and childhood shows that the socio-economic living conditions of the population, including material security, housing, working conditions, recreation, education, culture, traditions, nutrition, and other factors, directly and indirectly affect the health of future generations.
Keywords: USSR, Uzbekistan, Kashkadarya, Surkhandarya, obstetrician, gynecologist, pediatrician, village, personnel, consultation center.